Advances in regression, survival analysis, extreme values, markov processes and other statistical applications - Caeiro, Frederico; Natario, Isabel; Braumann, Carlos A.; Lita da Silva, Joao (Studies in Theoretical and Applied Statistics, 2013)
This volume of the Selected Papers from Portugal is a product of the Seventeenth Congress of the Portuguese Statistical Society, held at the beautiful resort seaside city of Sesimbra, Portugal, from September 30 to October 3, 2009. It covers a broad scope of theoretical, methodological as well as application-oriented articles in domains such as: Linear Models and Regression, Survival Analysis, Extreme Value Theory, Statistics of Diffusions, Markov Processes and other Statistical Applications.